2019
DOI: 10.5194/esd-2019-23
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Projecting Antarctica's contribution to future sea level rise from basal ice-shelf melt using linear response functions of 16 ice sheet models (LARMIP-2)

Abstract: Abstract. The sea level contribution of the Antarctic ice sheet constitutes a large uncertainty in future sea level projections. Here we apply a linear response theory approach to 16 state-of-the-art ice sheet models to estimate the Antarctic ice sheet contribution from basal ice shelf melting within the 21st century. The purpose of this computation is to estimate the uncertainty that arises from large uncertainty in the external forcing that future warming may exert onto the ice sheet. While ice shelf melting… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 98 publications
1
11
0
Order By: Relevance
“…Currently the ice sheets on Antarctica and Greenland have a net mass loss and contribute increasingly to sea level 10 rise (Rignot et al, 2014;Shepherd et al, 2018;WCRP Global Sea Level Budget Group, 2018;Eric Rignot, 2019;Mouginot et al, 2019). The ice sheet's future mass loss is important for sea level projections (Church et al, 2013;Ritz et al, 2015;Golledge et al, 2015;DeConto and Pollard, 2016;Mengel et al, 2016;Kopp et al, 2017;Slangen et al, 2017;Golledge et al, 2019;Levermann et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Currently the ice sheets on Antarctica and Greenland have a net mass loss and contribute increasingly to sea level 10 rise (Rignot et al, 2014;Shepherd et al, 2018;WCRP Global Sea Level Budget Group, 2018;Eric Rignot, 2019;Mouginot et al, 2019). The ice sheet's future mass loss is important for sea level projections (Church et al, 2013;Ritz et al, 2015;Golledge et al, 2015;DeConto and Pollard, 2016;Mengel et al, 2016;Kopp et al, 2017;Slangen et al, 2017;Golledge et al, 2019;Levermann et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…(1)). A more detailed description of the set-up (which is consistent with the one used for the LARMIP-2 (Levermann et al, 2019) and ABUMIP (Sun et al, J. Glaciol., in preparation) initiatives) will be given elsewhere (Greve et al, Geosci.…”
mentioning
confidence: 99%
“…MISMIP+ (Cornford et al, 2020), LARMIP (Levermann et al, 2019), ABUMIP (Pattyn et al, 2019), and ISMIP6 (Nowicki et al, 2020;Seroussi et al, 2020)), CISM has been shown to perform well compared to other higher-order ice sheet models, some that use resolutions of 1 km or higher in the region containing the grounding line. For the experiments described here, the model was run with the following options:…”
Section: Ice Sheet Model Configurationmentioning
confidence: 99%
“…For each CISM ensemble member, we apply a unique basal melt rate anomaly to each of five basins, following the LARMIP region delineation (Levermann et al, 2019). The regions are the Antarctic Peninsula, Weddell Region, East Antarctica, Ross Region, and Amundsen Region (Fig 4).…”
Section: Ensemble Designmentioning
confidence: 99%
See 1 more Smart Citation